2010
DOI: 10.1111/j.1742-4658.2009.07473.x
|View full text |Cite
|
Sign up to set email alerts
|

Restriction point control of the mammalian cell cycle via the cyclin E/Cdk2:p27 complex

Abstract: Numerous top-down kinetic models have been constructed to describe the cell cycle. These models have typically been constructed, validated and analyzed using model species (molecular intermediates and proteins) and phenotypic observations, and therefore do not focus on the individual model processes (reaction steps). We have developed a method to: (a) quantify the importance of each of the reaction steps in a kinetic model for the positioning of a switch point [i.e. the restriction point (RP)]; (b) relate this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 38 publications
0
51
0
1
Order By: Relevance
“…p27 level have been proposed as prognostic and therapeutic marker in many different human malignancies. 5 The increased mechanistic knowledge on its regulation revealed that additional determination of its localization is of prognostic value. 5 Future studies should reveal if the determination of p27 tyrosine phosphorylation could improve its potential value to serve as prognostic and/or therapeutic marker in human hyperproliferative disorders.…”
Section: Jak2 Binds and Directly Phosphorylates P27mentioning
confidence: 99%
See 1 more Smart Citation
“…p27 level have been proposed as prognostic and therapeutic marker in many different human malignancies. 5 The increased mechanistic knowledge on its regulation revealed that additional determination of its localization is of prognostic value. 5 Future studies should reveal if the determination of p27 tyrosine phosphorylation could improve its potential value to serve as prognostic and/or therapeutic marker in human hyperproliferative disorders.…”
Section: Jak2 Binds and Directly Phosphorylates P27mentioning
confidence: 99%
“…3 Controlling Cdk kinase activities, p27 level, localization and activity in mid-G 1 phase can directly influence passage through the restriction point. 4,5 Multiple mitogenic and antiproliferative signal transduction pathways can regulate p27 synthesis, stability, localization or activity. As they converge at the level of p27 regulation, this may serve as a platform to process and integrate diverse mitogenic and antimitogenic signals.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, MCA has been extended [67,[105][106][107] and applied to periodic phenomena such as glycolytic oscillations [108,109] and the cell cycle [110], to transient phenomena such as transient phosphorylation of signaltransduction proteins [111] and even to bistability [112]. It is especially interesting to consider such dynamic generalizations in a control systems context [113,114].…”
Section: Robustness and Fragilitymentioning
confidence: 99%
“…The growth inhibitory effect of mifepristone on ovarian cancer cells is associated with inhibition of DNA synthesis, down-regulation of the transcription factor E2F1 needed for S phase progression, and inhibition of the activity of Cdk-2. This cell cycle regulatory protein is critical to promote the transition of cells in the cell cycle from G1 to S phase (Conradie et al,2010). For instance, the activity of Cdk-2 is needed for the stimulation of histone gene transcription (Zhao et al,2000), which is one of the major events marking the entry into the S phase.…”
Section: Cell Cycle Arrestmentioning
confidence: 99%
“…For instance, the activity of Cdk-2 is needed for the stimulation of histone gene transcription (Zhao et al,2000), which is one of the major events marking the entry into the S phase. To drive cell cycle progression, Cdk-2 should be free of p21 cip1 and p27 kip1 binding (Conradie et al,2010), bound to cyclin E, and allocated to the nucleus to phosphorylate cell cycle regulatory proteins (Brown et al,2004;Lents et al,2002). Mifepristone, ORG-31710 and CDB-2914 affect the nucleocytoplasmic trafficking of Cdk inhibitors p21 cip1 and p27 kip1 , Cdk-2 and its co-factor cyclin E. The antiprogestins also increase p21 cip1 and p27 kip1 abundances in both cytoplasm and nuclear compartments in correlation with decreased Cdk-2 and cyclin E nuclear levels, increased cytoplasmic cyclin E, and a remarkable decline in the activity of Cdk-2 in both subcellular compartments (Goyeneche et al,2007;Goyeneche et al,2011).…”
Section: Cell Cycle Arrestmentioning
confidence: 99%